2008
DOI: 10.1002/cne.21672
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde analyses of spinothalamic projections in the macaque monkey: Input to the ventral lateral nucleus

Abstract: The distribution of retrogradely labeled spinothalamic tract (STT) neurons was analyzed in monkeys following variously sized injections of cholera toxin subunit B (CTb) in order to determine whether different STT termination sites receive input from different sets of STT cells. This report focuses on STT input to the ventral lateral nucleus (VL), where prior anterograde tracing studies identified dense or moderately dense STT terminations. Large and very large injections in VL produced large numbers of labeled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 76 publications
2
19
0
Order By: Relevance
“…Although at this point a consensus has been reached that Vim is the recipient of cerebellar input, the argument among investigators who probe the human thalamus during stereotactic interventions (Ohye et al, 1989;Lenz et al, 1990) has been focused on whether it also receives a direct overlapping spinothalamic input or whether the latter is confined only to the somatosensory territory posterior to the cerebellar afferent zone. Both neurophysiological and neuronatomical animal studies, and especially the most recent ones, are coming to agreement that there is an overlap of the direct spinothalamic and cerebellothalamic afferents in VL and especially in its ventral part (for review see Craig, 2008). In view of the existing evidence and the overall similarity between monkeys and humans regarding the topographic relationships of the territories of subcortical afferents in the thalamus, this can be extrapolated to the human thalamus with a high degree of confidence.…”
Section: Non-gabaergic Markers and Nuclear Delineationsmentioning
confidence: 90%
See 1 more Smart Citation
“…Although at this point a consensus has been reached that Vim is the recipient of cerebellar input, the argument among investigators who probe the human thalamus during stereotactic interventions (Ohye et al, 1989;Lenz et al, 1990) has been focused on whether it also receives a direct overlapping spinothalamic input or whether the latter is confined only to the somatosensory territory posterior to the cerebellar afferent zone. Both neurophysiological and neuronatomical animal studies, and especially the most recent ones, are coming to agreement that there is an overlap of the direct spinothalamic and cerebellothalamic afferents in VL and especially in its ventral part (for review see Craig, 2008). In view of the existing evidence and the overall similarity between monkeys and humans regarding the topographic relationships of the territories of subcortical afferents in the thalamus, this can be extrapolated to the human thalamus with a high degree of confidence.…”
Section: Non-gabaergic Markers and Nuclear Delineationsmentioning
confidence: 90%
“…In rhesus monkey, in the nomenclature of the atlas by Ilinsky et al (2002a), most cerebellothalamic fibers terminate in the ventral lateral (VL) and the centrolateral (CL) nuclei, both of them also receiving direct spinothalamic input; the major recipients of pallidothalamic fibers are the pars densicellularis and pars parvicellularis of the ventral anterior nucleus (VApc/VAdc) and the centromedian nucleus (CM); nigrothalamic fibers terminate in the pars magnocellularis of the ventral anterior nucleus (VAmc; for review see Asanuma et al, 1983;Kultas-Ilinsky, 1987, 2002b;Mackel et al, 1992;Sakai et al, 1996;Mackel, 2001;Stepniewska et al, 2003;Craig, 2008;Evrard and Craig, 2008). Moreover, with these subcortical inputs as criteria, the medial dorsal nucleus (MD) can also be considered a member of this nuclear group, because its two subdivisions, MDmf (pars multiformis) and MDmc (pars magnocelularis), receive an input from the substantia nigra , whereas the two others, pars parvicellularis (MDpc) and pars densicellularis (MDdc), receive cerebellar input (Middleton and Strick, 1997;Mason et al, 2000).…”
mentioning
confidence: 99%
“…The mean conduction velocity of marginal zone and deeper cells was 28.0 Ϯ 11.6 and 34.2 Ϯ 7.4 m/s, respectively. Previous studies have shown a small projection of the STT to ventral lateral (VL) nucleus in cats (Jones and Burton 1974) and primates (Boivie 1979;Craig 2008). In this study, we did not surround the rostral end of axons that were antidromically activated in VPL.…”
Section: Data Analysesmentioning
confidence: 56%
“…2a and b) suggests no prevailing fixed modality but a dominant TCD-related plastic phenomenon in the two patient groups examined. The presence of dominant somatosensory responses in NP patients is particularly striking because these nuclei receive little, if any, peripheral input (Stepniewska et al 2003;Craig 2008) and project dominantly to premotor and supplementary motor cortex (Matelli and Lupino 1996;Rouiller et al 1999;Morel et al 2005). Some factors could lead to a "misplacement" of the electrode more posteriorly and laterally into VLp or VPL, which receive somatosensory inputs.…”
Section: Interpretation Of the Resultsmentioning
confidence: 99%